2011
DOI: 10.1007/s10265-011-0438-6
|View full text |Cite|
|
Sign up to set email alerts
|

Response of plasma membrane H+-ATPase to low temperature in cucumber roots

Abstract: The effect of low temperature (LT, 10°C) on modification of plasma membrane (PM) H(+)-ATPase (EC 3.6.3.14) activity in cucumber roots was studied. Plants were grown under LT for 3 or 6 days. Some of the plants after 3 days exposure to LT were transferred to control conditions for another 3 days (post-cold, PC). The activity of PM-H(+)-ATPase was decreased in plants treated for 3 days with LT. However, the activity of PM-H(+)-ATPase was higher in plants treated with LT for a longer time and in PC plants as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 61 publications
(75 reference statements)
0
30
0
Order By: Relevance
“…Membranes are most susceptible to damage resulting from low temperature [41]. MDA is considered a final decomposition product of polyunsaturated fatty acids and it is used to determine oxidative damage [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membranes are most susceptible to damage resulting from low temperature [41]. MDA is considered a final decomposition product of polyunsaturated fatty acids and it is used to determine oxidative damage [42].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in permeability related to membrane damage and a change in its viscosity and fluidity are observed in plants that have been subjected to low temperature [41]. Increased generation of a proton gradient by PM H + -ATPase is required to maintain ionic balance and replenish the loss of organic compounds [58].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its importance, H þ -ATPase activity has to be modulated to deal with environmental stress conditions and metabolic changes. Recent evidence has shown that the H þ -ATPase is very sensitive to abiotic stresses, such as salinity, drought and temperature (Gong et al, 2010;Wakeel et al, 2010;Janicka-Russak et al, 2012Kim et al, 2013), even though its role in the plant response has not yet been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in H ? -ATPase activity have also been reported (Jian et al 1982;Ishikawa and Yoshida, 1985;White et al 1990;Martz et al 2006;Zhang et al 2006;Shi et al 2008;Janicka-Russak et al 2012;Kim et al 2013;Oh et al 2014;Zhou et al 2014). The mechanisms behind these changes are not yet known in detail, but cold acclimation seems to be associated with modifications of the membrane lipid composition and their effects on the PM H ?…”
Section: Interaction With Glycerolipids: the Real World Of The Membramentioning
confidence: 82%